The Aftermath of Management Actions on Competitive Advantage through Process Attributes at Food and Beverage Industries Export Import in Perak Harbor of Surabaya - Daengs, G.S. Achmad; Istanti, Enny; Kusuma Negoro, R.M. Bramastyo; Sanusi, Ruchan (International Journal of Criminology and Sociology, 2022)
The objectives of this study is to analyze information quality, customer relationship management on product quality, responsiveness, competitive advantage. This research type is a causal research with a quantitative approach. Population obtained from 82 export and import businessmen in Perak. Sample of study was taken with a saturated sampling technique, so the number of samples was 82 people. Data collection was carried out using a questionnaire. The data analysis technique used is PLS analysis. The results in this study indicate that: (1) information quality has a significant effect on product quality; (2) information quality has a significant effect on responsiveness; (3) customer relationship management has a significant effect on responsiveness; (4) product quality has a significant effect on responsiveness; (5) product quality has a significant effect on competitive advantage; (6) responsiveness has a significant effect on competitive advantage.